Rancangan Aplikasi Smart-Senyum Untuk Deteksi Dini Kesehatan Mental - Nawindah Nawindah; Setiawati Intan Savitri; Retno Wulandari (Jurnal Ilmiah Teknologi Infomasi Terapan, 2023)
Mental health for teenagers needs attention, especially for students with non-formal education (Sanggar Kegiatan Belajar 26 Bintaro). Everyday problems, at school and at work, are triggers for students to experience mental health problems. Mental health education is very necessary, considering that there are no mental health services and no guidance and counseling teachers, as well as tools to help carry out early detection. The design of the Smart-smile application was built using a prototype method to help carry out early detection. The measuring tool used in screening is the Self Reporting Questionnaire-20 (SRQ-20). By using the Smart Smile application, early detection of mental health can be easily done.